2017
DOI: 10.1044/2016_ajslp-15-0089
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Parent-Report Measures of Social Communication in Toddlers With and Without Autism Spectrum Disorder Across Race/Ethnicity

Abstract: Purpose This study investigated whether measures of early social communication vary among young children of diverse racial/ethnic status with and without autism spectrum disorder (ASD). Method Participants were 364 toddlers between ages 18 and 36 months with a diagnosis of ASD confirmed ( n = 195) or ruled out ( n = 169), from 3 racial/ethnic categories: non-Hispanic White ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 68%
“…This reality brings new challenges for professionals working in the ield of health and education. Based on what is already happening in other countries [25], it is necessary to establish public proposals that guarantee the access of this population to basic services through culturally appropriate strategies. Speciically, the speech therapist must improve instruments and procedures that are eicient to distinguish what is characteristic of social adaptation, which is part of the heritage of culture, the native language, and what is really a communication disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S. sample, difference between the Hispanic and non-Hispanic was only found for the Treatment (TR) subscale. Ethnic disparities between Hispanic and non-Hispanic groups in the United States have been frequently documented, including ASD prevalence, age of diagnosis, access to services (Baio et al, 2018; Magaña et al, 2013; Mandell et al, 2009), and symptom presentation (Harrison, Long, et al, 2017; Stronach & Wetherby, 2017). The current result is in line with the finding that compared with non-Hispanic mothers, Hispanic mothers have fewer sources of knowledge after their child diagnosed with ASD, which accumulates to unmet treatment needs (Magaña et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The boundaries between different versus disordered social communicative behaviors are influenced by cultural values and expectations (Bruner, 1990). Impairments in social aspects of communication are a diagnostic indicator of ASD (American Psychiatric Association, 2013), but much of what is known regarding parent report of early red flags related to ASD, such as language development, diminished eye gaze, use of gestures, and joint attention, has been derived from research on parents from English-speaking American backgrounds (Stronach & Wetherby, 2017; Wetherby et al, 2004). There is increasing recognition that application of currently established diagnostic criteria, including symptoms of ASD and assessment practices, may have limitations when used with children from CALD backgrounds (Harris, Barton, & Albert, 2014; Norbury & Sparks, 2013).…”
Section: Discussionmentioning
confidence: 99%